Seroprevalence of human T-cell lymphotropic virus I and II (HTLV I/II) among blood donors in a public blood center of Sergipe State, northeastern Brazil - Santos, Cibele Macedo; Aguiar, Rafael de Souza; Bencz, Ester; Amorim, Vanessa Oliveira; Góes, Marco Aurélio de Oliveira; Barreto, Íkaro Daniel de Carvalho; Ramos, Edivan Rodrigo de Paula (Brazilian Journal of Sexually Transmitted Diseases, 2019)
Introduction: Human T-cell Lymphotropic Virus types I/II (HTLV-I/II) have heterogeneous distribution worldwide and are endemic in some places. Both viruses can be sexually transmitted through blood transfusions, shared use of syringes and needles, and from mother to child during pregnancy, breastfeeding, and at the time of delivery. In Brazil, HTLV I/II screening has been part of the mandatory national blood donation since 1988. Objective: This study aimed to analyze the prevalence of HTLV I and II antibodies in blood donors residing at the state of Sergipe. Methods: This is an observational epidemiological study performed with the results of HTLV I/II screening serology of blood donors at the public blood center of the state of Sergipe, from January 1st, 2007 to December 31st, 2018. Statistical analysis was performed with the use of free software R, and descriptive analysis and evaluation of the trend of seroprevalence for HTLV I/II in the period. Results: Of the 303,589 blood samples analyzed, 691 (0.23%) were positive for HTLV I/II, with the highest prevalence among females (0.29%). Prevalence increased with age, reaching 0.40% of 50-year-old and older people. Replacement donors had a higher prevalence (0.28%), compared to volunteers (0.17%) and those summoned (0.06%). There was a steady trend in prevalence between 2007-2011, decreasing from 2012-2018. Conclusion: The findings also indicate factors associated with a higher prevalence of HTLV I/II, such as gender and age group. Despite the current decreasing trend among donors, it is important to evaluate populations other than blood donors, as the donor selection criteria influence the positivity of the samples.